Stakeholder management - Wasieleski, David M.; Weber, James, active 2017 (Business and society 360,, 2017)
Stakeholder theory is used for many purposes in a wide array of disciplines. It was intended to serve as a strategic management tool for business and society relationships in a capitalist system. While it has broad scholarly appeal, it is still somewhat controversial and is considered to be empirically underdeveloped. This new book offers a series of ten chapters from well-known, established and emerging business and society scholars working with stakeholder theory in its many aspects. Each chapter is centered on a different sub-topic related to stakeholder management, written by the actual published experts on that sub-topic. The chapters stand alone as comprehensive pieces of scholarship in themselves, but they are intimately related and interwoven so as to give readers an overall sense of cohesion around the area of stakeholder management.